Yeokwisan, a Standardized Herbal Formula, Enhances Gastric Emptying via Modulation of the Ghrelin Pathway in a Loperamide-induced Functional Dyspepsia Mouse Model - Hwang, Seung-Ju; Wang, Jing-Hua; Lee, Jin-Seok; Lee, Hwa-Dong; Choi, Tae-Joon; Choi, Seo-Hyung; Son, Chang-Gue (Frontiers in Pharmacology, 2021)
Background: Yeokwisan, a standardized herbal formula, has exhibited clinical benefit for patients suffering from refractory functional dyspepsia (FD) in Korea since 2016. However, data about the mechanism of action of this formula are yet not available. Aim of the study: To evaluate and explore the effects of Yeokwisan on gastric emptying, a major symptom of functional dyspepsia, and its underlying mechanisms of action using a mouse model. Materials and methods: BALB/C mice were pretreated with Yeokwisan (100, 200, and 400 mg/kg, po) or mosapride (3 mg/kg, po) for 5 days and then treated with loperamide (10 mg/kg, ip) after 20 h of fasting. A solution of 0.05% phenol red (500 μL) or diet of 5% charcoal (200 μL) was orally administered, followed by assessment of gastric emptying or intestinal transit. Plasma acyl-ghrelin (ELISA), C-kit (immunofluorescence and western blotting), nNOS (western blotting) and gastric contraction- and ghrelin-related gene/protein expression levels were examined in stomach and small intestine tissues. Results: Loperamide injection substantially delayed gastric emptying, while Yeokwisan pretreatment (especially 200 and 400 mg/kg Yeokwisan) significantly attenuated this peristaltic dysfunction, as evidenced by the quantity of phenol red retained in the stomach (p < 0.05 or 0.01) and stomach weight (p < 0.05 or 0.01). The levels of plasma acyl-ghrelin and expression of gastric ghrelin-related genes, such as growth hormone secretagogue receptor (GHSR), ghrelin-O-acyltransferase (GOAT), adrenergic receptor β1 (ADRB1) and somatostatin receptor (SSTR), were significantly normalized (p < 0.05 or 0.01) by Yeokwisan (400 mg/kg). Yeokwisan (400 mg/kg) significantly tempered the loperamide-induced alterations in the c-kit and nNOS levels (p < 0.01) as well as the expression of contraction- and ghrelin-related genes, such as 5-HT4 receptor (5-HT4R), anoctamin-1 (ANO1), ryanodine receptor 3 (RYR3) and smooth muscle myosin light chain kinase (smMLCK), in the stomach, but not in the small intestine. Conclusion: The present results showed the clinical relevance of Yeokwisan, in treating FD, especially in promoting gastric emptying but not small intestinal transit. The main mechanisms corresponding to these effects may involve the modulation of the ghrelin pathway and activation of interstitial cells of Cajal in stomach tissue.